A Preliminary Exploration of the Influence of Greek Philosophy on Early Childhood Education: An Application in Hong Kong - Lau, Grace; Ho, Kwok Keung (Έρευνα στην Εκπαίδευση, 2017)
The twentieth century saw great hopes but also great failures. Philosophy, however, by its timeless truth, might confront the ever changing fashion by giving people a pointer through its philosophical application in the realm of education. In this paper, the authors argue that many philosophical teachings from the famous Greek philosophers are indeed influential when their teachings are applied to the early childhood classrooms in Hong Kong. Their sphere of influence has extended from the British colonial period to the present era in Hong Kong as far as early childhood education is concerned. For Plato, his theory of Forms and his emphasis on the search of Truth will be compared with Aristotle empiricist views in his study of nature. While analyzing the theory of Forms and the idea of the Good, the authors found that Plato’s approach could be traced back to Xenophanes who proposed a monotheistic theory of God and is religiously related to Christianity. Their applications in the top-down teacher-directed play-based curriculum were valid in the early childhood educational mode during the early colonial period to the 1980s in Hong Kong. Since Aristotle was found to have a different approach to Forms as compared to those of Plato, Aristotle’s argument for Forms was mentioned and its relevancy to the prevalent hybrid mode of the play-work-based curriculum in early childhood education is explored. Following the most recent reform in early childhood education in Hong Kong, free play is recommended in the reform document. Heraclitus’s doctrine of ‘flux’ could apply most suitably in the free play condition as ‘flux’ signifies an ever changing condition just as the nature of free play does. A final touch of this paper is on exploring the divergent views of Plato and Aristotle and their impacts on education today so as to provoke further thoughts of the readers in the areas explored.